Er(r)go... - Kalaga, Wojciech (Er(r)go. Teoria - Literatura - Kultura, 2017)
Er(r)go… , difficult, difficult times for the humanities, “frail and divided within,” difficult for literary studies, bound by “an ontological corset.” And then, the theoretical impasse: the question about the epistemological potential of the poststructuralist paradigm. Farewell to Derrida? The French theory – an American construct. How to think: ahead or backwards? And Nietzsche is best treated with Nietzsche. Is “prosopopeia of another’s tongue” leading us towards or away from the humanities? Turns, paradigm changes, turns, returns – with corrections – and best of all, a turn away from all turns and a return to philology. The appetite for philology and close-reading is growing. Read, one must read and observe texts in the world. Here arises a dispute over the reading distance – which kind of reading is superior? Close, long, or perhaps middle-distance? And how to distinguish literature from the description of soil erosion in Nebraska? Ask Eagleton. And what if interpretation is an expression of naivety and exaltation? Get to work, literary studies! To work as a text-process, not merely a text-result, to writing, not merely to reading. Here lies the pleasure of pre-texts, consorting with the draft, surrounded by fore-texts, draft projections, draft pre-incarnations of the text, draft close-reading, studying the draft, draft history of the text, meta-draft research and Polish draft studies. The genetics of text and genetics of prints; the flowing and ebbing of meaning, hermeneutics of invention, uncertain determinations. The responsibility of “the I-who-reads” towards the “I-who-is-read.” In the meantime, the death of a professional critic, because who needs literary criticism today? Social redundancy? Where are the critics who understand their task as metaphysical – as serving the word of the Other? In their place, weak professionalism. Atrophy of literary communication, a deluge of quasi-literary works, pauperization of the readers’ competence. So, the idiom of slack (for masses), or a voice of reflection? “A vigorous corpse” in the gray zone between the market and the university. Liberation? But, at the end of the day, the return to centralism. Birth of the author, when was that? And now, after his own death, the author finally returns (the assassin resting in his grave for years). It is now possible to peep on the writer in a closed room, as if in a psycho-anthropological laboratory, and search for the universal laws of human creativity. But one must be careful: after death, the archive is not a workshop; a workshop is always dynamic. Herbert’s vertical notes and the “spreading of the great parable,” five loose pages, Nepenthes Family and Linnaeus, and earlier, a notebook. “Revisionary expanse” of Virginia Woolf’s archive. McLuhan, Gutenberg and a typographical man. Packaged doses of philosophy, the book as a very problematic device and a fatal medium. McLuhan talks to Playboy reporter and Pascal lies down on the Gutenbergian Procrustean bed to torture his own spirit. A fractioned man, dismembered by the alphabet, sliced into pieces by print. Streams of knowledge, like grape must, flowing from under the press (printing one, naturally). And here and there, semiotic absolutism, theoretical dogmatism, the hope of saving one’s own name, cultural recontextualisations, a young wife and ridiculous interpretative errors, cultural studies over copyright, doxa as the voice of the people, medialised and mediatised mind of don Quixote, the art of textual analysis like folk dancing, becoming similarly extinct, a sovereign reader, a pink pirate and the praise of the unproductive. And the subject is travelling from Silesia to Warsaw through Ustrzyki Dolne. The present issue is guest-edited by Professor Adrian Gleń from the University of Opole, Poland. Wojciech Kalaga